Split-Brain Babies? Differences in Representation of Bilaterally and Unilaterally Presented Visual Stimuli in Infancy - Scott, Kimberly M. (Frontiers in Psychology, 2019)
Information needed for perception and action is often distributed across the two hemispheres of the human brain. During development, representations lateralized due to topographic sensory maps may be available independently before they can be integrated across hemispheres. These studies (total N = 211) investigate visual interhemispheric integration in two domains in infancy. In Experiment 1, infants (8-14 months) showed stronger evidence of representing the equality of two shapes when the shapes were presented in the same visual hemifield. In Experiments 2-4, infants (10-19 months) showed evidence of greater familiarization when shown 16 dots in one hemifield than when shown 8 dots in each hemifield. The possibility that interhemispheric integration poses an unusually late-resolved challenge in infant vision is discussed.